2007
DOI: 10.1007/s10463-007-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

On a simple strategy weakly forcing the strong law of large numbers in the bounded forecasting game

Abstract: Azuma-Hoeffding-Bennett inequality, Capital process, Game-theoretic probability, Large deviation,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…We believe that this again shows effectiveness of game-theoretic proofs as we have shown in our previous works [4,5].…”
Section: Some Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We believe that this again shows effectiveness of game-theoretic proofs as we have shown in our previous works [4,5].…”
Section: Some Discussionsupporting
confidence: 77%
“…Then adjusting some constants we can assume hðxÞ $ x 2 for all x without loss of generality. Then and E 0 1 , E 3 , where E 0 1 is given in (4). Therefore Skeptic can force E 3 .…”
Section: Slln With a Single Hedgementioning
confidence: 98%
See 1 more Smart Citation
“…Since E 2 ⊂ E 1 , forcing E 2 is stronger than forcing E 1 . However the multiplicative strategy in Subsection 2.1 is of interest, because it is a contrarian counterpart of the momentum strategy studied in [2].…”
Section: Contrarian Strategiesmentioning
confidence: 99%
“…It is only natural to expect that stronger results require more complicated strategies by Skeptic. For example in [2] we have shown that a simple strategy of Skeptic based on the past average of the moves by Reality forces SLLN for the case of bounded Reality's moves. However if Reality's moves are unbounded, strategies for forcing SLLN are much more complicated as discussed in [4].…”
Section: Introductionmentioning
confidence: 99%